If y varies inversely as the cube of x and directly as the square of z and y = -6 when x=3 and z =9, how do you find y when x =6 and z= -4?

Answer 1
If y varies inversely as the cube of x and directly as the square of z then we can write: #color(white)("XXXXX")##(y*x^3)/(z^2) = c# for some constant #c#
If #color(white)("XXXXX")##(x,y,z) = (3,-6,9)# is a solution for this equation, then
#color(white)("XXXXX")##((-6)*3^3)/(9^2) = c# #color(white)("XXXXX")##=162/81 = c# #color(white)("XXXXX")##c= 2#
When #(x,z) =(6,-4)# #color(white)("XXXXX")##(y*x^3)/(z^2) = 2# becomes #color(white)("XXXXX")##(y*216)/16 = 2#
#color(white)("XXXXX")##y = (16*2)/(216)#
#y = 4/27#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find y when x = 6 and z = -4, we can use the inverse variation formula.

First, let's find the constant of variation (k) by substituting the given values into the equation y = k * (x^3) / (z^2).

-6 = k * (3^3) / (9^2)

Simplifying this equation, we get:

-6 = k * 27 / 81

Next, we can solve for k:

k = -6 * 81 / 27

k = -18

Now that we have the value of k, we can substitute it into the equation and solve for y when x = 6 and z = -4:

y = -18 * (6^3) / (-4^2)

Simplifying this equation, we get:

y = -18 * 216 / 16

y = -243

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find ( y ) when ( x = 6 ) and ( z = -4 ), you can use the concept of inverse and direct variation.

Given that ( y ) varies inversely as the cube of ( x ) and directly as the square of ( z ), we can set up the equation:

[ y = k \times \frac{z^2}{x^3} ]

First, we need to find the constant of variation, ( k ), using the initial values provided:

[ -6 = k \times \frac{9^2}{3^3} ]

Solving for ( k ):

[ k = \frac{-6 \times 3^3}{9^2} ]

[ k = -6 \times \frac{27}{81} ]

[ k = -2 ]

Now that we have ( k ), we can use it to find ( y ) when ( x = 6 ) and ( z = -4 ):

[ y = -2 \times \frac{(-4)^2}{6^3} ]

[ y = -2 \times \frac{16}{216} ]

[ y = -2 \times \frac{2}{27} ]

[ y = -\frac{4}{27} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7